Mechanical aspects of semi-circular sandstone fractured specimens with U-notch in the presence of various bedding angles. (April 2023) - Zhou, Yuguo; Hao, Ruiqing; Zhao, Feiyang; Liao, Lin; Li, Wenpu
Highlights: Fracture loads are obtained from experiments performed on SCB and USCB specimens with different bedding angles. Effects of notch tip radius and bedding angle on fracture loads are explored experimentally. The transversely isotropic material is used to consider the material anisotropy. Theory of transverse isotropic materials combined with two theoretical criteria could well predict the fracture toughness of the material. Failure modes of SCB and USCB with different bedding angles are summarized. Abstract: In tunnel and underground structures, the deformation and damage of layered rock masses often exhibit substantial anisotropy, where the fracture pattern of layered rock masses containing notched cracks directly influences the construction stability of the project. By this virtue, this paper presents a theoretical formulation of the fracture toughness of anisotropic rock materials containing U-notches on the basis of the constitutive model of transversely isotropic materials. The anisotropic influence coefficients are also appropriately incorporated into the formulas of the point stress (PS) and mean stress (MS) criteria to obtain their corresponding modified relations. The fracture toughness ( KIC ) of sandstones with bedding angles is evaluated by utilizing semi-circular bend (SCB) and U-notched semi-circular bend (USCB) specimens. The theoretically obtained results and experimentally observed data display that the fracture toughness of the specimens gradually decreases with increasing bedding angle, irrespective of the notch tip radius. Further, the results of the mean stress criterion are closer to the experimental data in comparison with those of the point stress criterion. Additionally, the fracture damage patterns pertinent to the SCB and USCB sandstone specimens with various bedding angles are displayed and discussed. The achieved results could provide a solid basis for better realizing the engineering deformations and failure analyses of layered sandstones.